(untitled) - Hanks, Lucien M. (Chicago, 1972)
Part 1. Bang chan and the cultivation of rice; Part 2. Adaptations to a changing environment;...
Keywords: Sinh thái nông nghiệp,Agricultural ecology,Agricultural ecology; Thái Lan,Thailand,Thailand